Functional Performance and Tendon Morphology After Operative or Nonoperative Treatment of Achilles Tendon Ruptures - Sophie Zhu; Josh Garofalo; Monther Abuhantash; Sheila McRae; Peter MacDonald; Rob Longstaffe; Dan Ogborn (International Journal of Sports Physical Therapy)
# Background